PENGARUH METODE DISCOVERY LEARNING TERHADAP HASIL BELAJAR PKN DAN MOTIVASI BELAJAR SISWA KELAS V SDN II TAMENG GIRIWOYO - Paradika Angganing (Universitas PGRI Yogyakarta, 2016)
This study aims 1) to determine the effect of the Discovery Learning method forlearning outcomes PKN class V SDN II Tameng Giriwoyo, 2 ) the influence ofDiscovery Learning Method on motivation in class V SDN II Tameng Giriwoyo. Thisresearch is a quasi experiment. The population in this study were all students of SDN IITameng and the sample is a class V SDN II Tameng Giriwoyo. Data were collectedthrough tests to see student learning outcomes and questionnaires and observation to seethe effect of the Discovery Learning Methods and motivation on learning outcomes ofstudents of class V SDN II Tameng Giriwoyo . The results of the research are: 1) Thereis the effect of the Discovery Learning Method to the learning outcomes of studentsPKN Class V SDN II Tameng Giriwoyo 2 ) There is an effect Discovery Learningmethod to motivate students to learn PKN Class V SDN II Tameng GiriwoyoKeywords : Discovery Method of Learning, Motivation, Learning Outcomes